Sistem Pakar Rekomendasi Profesi Berdasarkan Multiple Intelligences Menggunakan Teorema Bayesian - Elvanisa Ayu Muhsina; Nurochman Nurochman (JISKA (Jurnal Informatika Sunan Kalijaga), 2017)
Intelligence is perhaps to be the one of the most logical way to determine how smart people is.  That fact has always been a problem at job because there are number of job that attract people but require a high GPA for them. Employee with high GPA doesn’t always fit in his skill and work role. They unable to understand and maintain their performance. This expert system is a necessary for recommend job using Intelligence. This research use a Bayesian theorem calculation to find out probability value and job recommendation. The value of MI (Multiple Intelligences)’s user, MI probability to a job and job probability to previous result without any evidence produce a Calculation Variable.Result of the test shows output recommendation as expert system to 81.25% match with expert recommendation. 100% users statistically states the system running well. Expert system usability test shows 80% users strongly agree, 15.7% users agree and 4.3% users are neutral.Keywords: Multiple Intelligences, Profession, Bayesian theorem